2022
DOI: 10.3389/fneur.2021.765962
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Carotid Artery Perivascular Fat Density and Embolic Stroke of Undetermined Source

Abstract: AimThis study aims to retrospectively evaluate the association between pericarotid inflammation and the presence of embolic stroke of undetermined source (ESUS).MethodsIn total, 126 patients with ESUS and 118 patients with ischemic stroke from large artery atherosclerosis (LAA) were enrolled. All the patients underwent brain MRI and a neck CT angiography (CTA) examination. Reviewers were blinded to infarct location and stroke cause. Paired t-tests assessed within-subjects differences in mean Hounsfield units (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, there have been a few studies investigating the possible effects of PVAT surrounding the carotid arteries. Hu et al found an elevated density of carotid artery PVAT on CT scans in patients with embolic stroke of unknown source [26]. Zhang et al found an independent association between carotid artery PVAT density and intraplaque hemorrhage analyzing CT and MRI scans [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been a few studies investigating the possible effects of PVAT surrounding the carotid arteries. Hu et al found an elevated density of carotid artery PVAT on CT scans in patients with embolic stroke of unknown source [26]. Zhang et al found an independent association between carotid artery PVAT density and intraplaque hemorrhage analyzing CT and MRI scans [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the inflammatory changes in PVAT surrounding the carotid artery can be evaluated using computed tomography angiography (CTA) as areas of increased perivascular fat density (PFD) [ 10 ]. Recent studies have provided evidence that the increased PFD of the carotid artery is associated with cerebrovascular ischemic symptoms, ischemic stroke from an undetermined embolic source, and the occurrence of intraplaque hemorrhage [ [11] , [12] , [13] ]. A thorough search of the literature shows that there is no incontrovertible evidence to show that PFD is related to early ISR after CAS.…”
Section: Introductionmentioning
confidence: 99%